FAKTOR PENYEBAB PENYIMPANGAN TATA RUANG (STUDI PEMBANGUNAN CONDOMINIUM) DI KOTA BANDUNG - Isradjuningtias, Agri Chairunisa (Faculty of Law, Parahyangan Catholic University, 2017)
Condominium development is the answer for those who need a place to live, but not a few whose development was violate the laws and regulations related to spatial planning, then this research is on behalf to anticipate the causes of spatial deviation by using socio legal research method. Based on the research that has been carried out found the factors that cause spatial deviation (Study of Condominium Development) in Bandung are Citizen Factors, Government Factors and Market Strength Factors in which these three factors are not stand-alone but become a linkage that can not be separated from one another.